Climate change impacts on Mediterranean small ruminant production systems and climate change mitigation options - del Prado A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The Mediterranean basin is warming faster than the rest of the planet. Average annual temperatures are now 1.4 °C higher than during the period 1880-1899, well above current global warming trends, especially during the summer. Depending on the climate scenario and on the season, a rise in temperatures from 2 to 6 °C by 2100 is expected. High temperature events and heat waves are likely to become more frequent and/or more extreme. A reduction in summer precipitation has already been observed and model simulations indicate that such tendency should persist. For each degree of global warming, mean rainfall will likely decrease by about 4% in most of the region, particularly in the south. Heavy rainfall events are likely to intensify in all seasons except in summer. Climate change in the Mediterranean basin has both direct and indirect effects on small ruminant systems. At the animal level, the increased temperature and radiation cause heat stress, which triggers behavioural and metabolic changes affecting animal health and welfare. Reproduction performance could be impaired by a reduced semen production and changes in the sexual activity of males, but also by a lower conception rate of females and lighter birth wight of lambs. Heat stress is usually associated with a low feed intake, and thus a reduced performance. Milk production could be reduced by 20-30%, with lower protein and fat concentrations and a reduction of coagulation properties in milk. Meat could develop an abnormal flavour, associated with a greater water holding capacity and a shorter shelf-life. In terms of feed supply, heat and water stress might modify the timing and length of plants’ growing season. The productivity of forage and cereals in rainfed conditions is expected to decrease. Warming and the higher CO2 concentration might decrease the nitrogen content of forage, but also favour nitrogen-fixing species (legumes), which could compensate for it. Thus, understanding and predicting the changing climatic patterns is increasingly important for Mediterranean farming sytems.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)